Characteristics of Pregnant Women at Risk of Child Stunting: A Descriptive Study in Stunting Locus Areas of Sorong Regency - Raisya Rahmawati Saufi; Jan Pieter E. A. Kambu; Atira Tilik Mayor; Harry Allan Papendang; Hamdiah Ahmar (Papua Medicine and Health Science, 2026)
Child stunting remains a major public health problem in Indonesia, including Sorong Regency. Maternal characteristics during pregnancy play an important role in fetal growth and may influence the risk of child stunting. This study aimed to describe the characteristics of pregnant women in the stunting locus areas of Sorong Regency. This descriptive observational study used secondary data from the Stunting Case Audit worksheets of the National Population and Family Planning Board (BKKBN) in Sorong Regency. A total of 178 pregnant women who met the inclusion and exclusion criteria were included, and the data were analyzed using univariate analysis with SPSS. Most respondents were aged 20–35 years (68.0%), lived in rural areas (60.1%), were unemployed (91.6%), and had low economic status (53.4%). The predominant maternal health characteristics included multiparity (48.9%), risk of chronic energy deficiency based on mid-upper arm circumference (71.3%), anemia during pregnancy (52.2%), iron supplementation (71.9%), fewer than four antenatal care visits (58.4%), and passive cigarette smoke exposure (65.7%). These findings indicate that pregnant women in the stunting locus areas of Sorong Regency were characterized by several maternal conditions requiring strengthened nutritional monitoring, anemia prevention, improved antenatal care utilization, and reduced cigarette smoke exposure as part of comprehensive child stunting prevention efforts.